The Palgrave Handbook of Holocaust Literature and Culture - Aarons, Victoria; Lassner, Phyllis (Springer International Publishing : Imprint: Palgrave Macmillan, 2020)
XIV, 840 p. 48 illus., 13 illus. in color.